PENGEMBANGAN INSTRUMEN DIAGNOSIS KESEHATAN SUPERVISI PEMBELAJARAN - Dithia Linggasari (Jurnal Tata Kelola Pendidikan, 2021)
The research entitled "Development of Learning Supervision Health Diagnostic Instruments". Participants in this study were three education management experts, 102 school principals, 317 teachers and 135 well-known administrators in public and private junior high schools (SMP) throughout Purwakarta Regency. The purpose of this study was to analyze the learning surveillance health diagnosis instrument, see the health picture of learning supervision at State and Private Junior High Schools (SMP) in Purwakarta Regency and follow up on the results of the learning supervision health diagnosis. This study uses a descriptive method with a quantitative approach. The technique of using data using a questionnaire. The instrument was developed based on the dimensions of the program, planning, implementation, evaluation and supervision reporting. As for the instrument development technique through construction tests with expert lecturers by revising the item questions, respondent construct tests by distributing questionnaires with the help of Google in the form of validity tests, reliability tests and Weight Mean Score. The researcher concluded that the output of this study was in the form of a learning supervision health diagnosis instrument that could be used as a research measurement tool and a measuring tool to diagnose the health of learning supervision consisting of instruments for the principal who handled 23 questions, the teacher entered 22 questions and the administration that was asked. 16 question items; health picture Learning Supervision in Public and Private Junior High Schools throughout Purwakarta Regency as a whole is in a very healthy condition and based on school accreditation is also in a very healthy condition; and follow-up on the results of the learning supervision health diagnosis in the form of maintenance and the current condition of the supervision of learning in schools for each and existing indicators.